Bear's House of Books - Bishop, Poppy; Edgson, Alison (Wilton, CT : Tiger tales, 2017)
Friends Fox, Rabbit, Hedgehog, and Mouse all love to read. One day, they find a book in the woods and set off to return it to its owner, Bear. When they arrive at Bears house, they discover shelves and shelves of books. A dream come true as they read story after story until Bear comes home! -- Amazon.com.
Keywords: Bears -- Juvenile fiction; Forest animals -- Juvenile fiction; Books and reading -- Juvenile fiction; Friendship -- Juvenile fiction; Bears -- Fiction; Forest animals -- Fiction; Books and reading -- Fiction; Friendship -- Fiction